Anne of Green Gables - Book 1 - Montgomery, L. M. 1874-1942. (Lucy Maud) (Philadelphia, PA : Courage Books, 1993)
Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her.
With an excerpt from the author's journal.
Keywords: Orphans -- Fiction; Friendship -- Fiction; Country life -- Fiction -- Prince Edward Island; Prince Edward Island -- Fiction